Effect of the reactants molar ratio on the kinetics of cycloaddition of 2,3-dimethylbuta-1,3-diene to methylacrylate - Kostiv, I. S.; Marshalok, G. A. (Видавництво Львівської політехніки, 2017)
The cycloaddition reaction between 2,3-dimethylbuta- 1,3-diene and methylacrylate proceeds by the second order kinetics. The rate constants increase with the increase in the excess of one of the reactants. The change in the effective rate constants is described by the Michaelis–Menten equation indicating that the reaction proceeds through the initial equilibrium stage of formation of an intermediate complex which then transforms into the product. The effective rate constants, the equilibrium constants of formation of the intermediate complex, and the rate constant of its transformation into the reaction product were determined, as well as the thermodynamic parameters of the formation of the intermediate complex and the activation parameters of the transformation of the intermediate complex into the product. The limiting stage of the reaction is established and itsmechanism is suggested.
Keywords: 2 3-dimethylbuta-1 3-diene; methylacrylate; methyl-3 4-dimethylcyclohex-3-ene-1-carboxylate; cycloaddition reaction; Michaelis–Menten equation; effective rate constants; intermediate complex; limiting stage